PENGARUH INNOVATION CAPABILITY TERHADAP FINANCIAL CAPABILITY : RESISTANCE TO CHANGE SEBAGAI MODERASI - Putri, Bella May Ranti; Pujianto, Wahyu Eko (Program Studi Pendidikan Tata Niaga Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2024)
Abstract Economically, Small and Medium Enterprises (SMEs) have a contribution to exploring the impact of financial innovation capabilities on the efficiency of economic change. It is hoped that the existence of SMEs in the regions can provide a positive contribution. The main focus of this research is to understand how the application of innovation capabilities can make a significant contribution to improving businesses in the long term. This research aims to determine the influence of innovation capability and innovation capability and financial capability on moderating resistance to change in the performance of SMEs in Candi District. This involved 63 SME owners consisting of food, beverage, service, industrial, material and agricultural businesses. This type of research is quantitative with an explanatory research approach. Data analysis used SmartPLS 04. The sampling method was by distributing questionnaires offline with a sample size of 63 respondents. Innovation capability has a positive impact on financial capability in moderating resistance to change in SMEs in Candi District.